(untitled) (Praxis Educativa, 2022)
The article describes in the university environment the new dynamics of communication of science in the framework of the Information and Knowledge Societies, which with the irruption of digital technologies transformed the habits of access and transmission of scientific knowledge, disseminated in its majority in speech and written culture. It will argue in a discursive way why it is necessary to explore new literacies and forms of multimodal textuality as emerging alternatives for the apprehension and dissemination of scientific knowledge, in contrast to the formats traditionally used by universities in the appropriation and dissemination of this knowledge and training. of professionals.